Autocrine regulation of human sperm motility by tachykinins - Pinto Francisco M; Ravina Cristina G; Subiran Nerea; Cejudo-Román Antonio; Fernández-Sánchez Manuel; Irazusta Jon; Garrido Nicolas; Candenas Luz (BMC, 2010)
Abstract Background We examined the presence and function of tachykinins and the tachykinin-degrading enzymes neprilysin (NEP) and neprilysin-2 (NEP2) in human spermatozoa. Methods Freshly ejaculated semen was collected from forty-eight normozoospermic human donors. We analyzed the expression of substance P, neurokinin A, neurokinin B, hemokinin-1, NEP and NEP2 in sperm cells by reverse-transcriptase polymerase chain reaction (RT-PCR), western blot and immunocytochemistry assays and evaluated the effects of the neprilysin and neprilysin-2 inhibitor phosphoramidon on sperm motility in the absence and presence of tachykinin receptor-selective antagonists. Sperm motility was measured using WHO procedures or computer-assisted sperm analysis (CASA). Results The mRNAs of the genes that encode substance P/neurokinin A (TAC1), neurokinin B (TAC3), hemokinin-1 (TAC4), neprilysin (MME) and neprilysin-2 (MMEL1) were expressed in human sperm. Immunocytochemistry studies revealed that tachykinin and neprilysin proteins were present in spermatozoa and show specific and differential distributions. Phosphoramidon increased sperm progressive motility and its effects were reduced in the presence of the tachykinin receptor antagonists SR140333 (NK1 receptor-selective) and SR48968 (NK2 receptor-selective) but unmodified in the presence of SR142801 (NK3 receptor-selective). Conclusion These data show that tachykinins are present in human spermatozoa and participate in the regulation of sperm motility. Tachykinin activity is regulated, at least in part, by neprilysins.